EFFECTIVENESS OF INTRUMENTAL MUSIC THERAPY TO DECREASE OF STRESS LEVELS IN STUDENT LEVEL STUDY END NURSING UNIVERSITY SAHID SURAKARTA - Bahri, Ahmad Syamsul; Pamungkas, Idris Yani (JURNAL ILMU KEPERAWATAN INDONESIA (JIKI), 2017)
.